Gradual south-north climate transition in the atlantic realm within the younger dryas - Zhang, Haiwei (2022)
The abrupt climate event Younger Dryas (YD) has been extensively studied; however, its structure is still poorly understood. Climate in northeastern Brazil is very sensitive to the latitudinal position of the intertropical convergence zone (ITCZ) associated with abrupt climate change in the Atlantic. Here, we report changes in the ITCZ position within the YD by using precise speleothem multiproxy records from northeastern Brazil. We provide evidence for a gradual northward migration of the ITCZ preceding poleward shifts of the westerlies and the polar front in northern high latitudes within the YD. This can be attributed to gradual increase in atmospheric CO2 concentration as a consequence of the weakening Atlantic Meridional Overturning Circulation (AMOC). We suggest that a persistent increase in atmospheric CO2 might have triggered a resumption of the AMOC and reorganization of the atmosphere circulation in the Atlantic during the mid-YD.